How Media Use Influences the Fertility Intentions Among Chinese Women of Reproductive Age: A Perspective of Social Trust - Ning, Chuanlin; Wu, Jing; Ye, Yijie; Yang, Nan; Pei, Huacheng; Gao, Hao (Frontiers in Public Health, 2022)
Background The low fertility level has become a serious social problem in China. Previous research has argued the significant influence of media use and social trust on fertility intentions, but the interaction between the two variables and how they influence fertility intentions remain further investigation. This study explored the influence mechanism of media use on Chinese women's fertility intentions from the perspective of social trust. Methods This study collected data from the 2017 China General Social Survey, investigated the relationships between variables through bivariate correlation coefficients, and explored the differences in fertility intentions among women of reproductive age (20–49). Also, this paper examined the influence of media use and social trust by regression analysis and tested the mediating role of social trust between media use and fertility intentions with Bootstrap sampling. Results Women with different media use preferences, education levels, and family incomes have significant differences (p < 0.01) in fertility intentions. New media use negatively influences women's fertility intentions, while traditional media use has no significant influence on women's fertility intentions. Social trust significantly influenced women's fertility intentions and partially mediated the impact of new media use on fertility intentions. Conclusion Online communication influences fertility intentions among Chinese women of reproductive age. It tends to influence their social trust by amplifying negative social news, affecting their fertility intentions further. This paper suggests the importance of strengthening social trust and online agenda-setting to improve women's fertility intentions that strategic information communication can change their perceptions of social trust.